Deciphering the Microbiome-Gut-Eye Axis: A Mendelian Randomization Analysis of the Causal Influence of Gut Microbiota on Myopia - Xu, Weicheng; Shi, Wei (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: GWAS